A proteomic portrait of atherosclerosis. - Eberini, I; Wait, R; Calabresi, L; Sensi, C; Miller, I; Gianazza, E (2013)
We have arranged in this review the main evidence about proteome alterations in different cell and body fluid compartments along the progression of atherosclerosis. With time the description of the molecular phenomena is becoming more and more detailed yet the complex interrelationships among different factors are still elusive and previously neglected aspects (such as size for lipoprotein particles) emerge as not less relevant than the absolute abundance of individual proteins. Physiological limits to the kinetics of protein distribution through the biological fluids seem to hinder the early diagnosis of acute conditions through plasma analysis but suggest urine analysis as a workable alternative for the assessment of chronic conditions. The survey of literature data is complemented with a few unpublished results from our laboratories, featuring 2DE maps of the proteins extracted from human thrombi.